Cardiac Chamber Quantification by Echocardiography in Adults: Recommendations from the Association of Cardiovascular Surgeons of Ukraine and Ukrainian Society of Cardiology - V. V. Lazoryshynets; V. M. Kovalenko; S. V. Potashev; S. V. Fedkiv; A. V. Rudenko; R. M. Vitovskiy; O. S. Sychov; S. A. Rudenko; Y. A. Ivaniv; O. A. Krikunov; O. A. Mazur; L. M. Hrubyak; et al. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Fast technology development over the past decade as well as changes in practical echocardiography (EchoCG) lead to have given rise to a need in the update of previous guidelines for cardiac chambers quantification, which was the aim of this publication by working group of the Association of Cardiovascular Surgeons of Ukraine and Ukrainian Society of Cardiology. This paper provides up-to-date evidence-based data regarding reference ranges for all cardiac chambers, including available data regarding 3D-echocardiography and myocardial deformation (strain), based on the wide range of studies of healthy individuals found in many databases in healthy individuals. In addition, this document contains an attempt to adjust several minor controversies from previous guidelines.This document is based on “Recommendations for Cardiac Chamber Quantification by Echocardiography in Adults: An Update from the American Society of Echocardiography and the European Association of Cardiovascular Imaging” (2015) adapted according to the local peculiarities and printed abridged. Full content of “Cardiac Chamber Quantifica-tion by Echocardiography in Adults: Recommendations from the Association of Cardiovascular Surgeons of Ukraine and Ukrainian Society of Cardiology” is available online at the official Website https://amosovinstitute.org.ua of the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine. This paper contains key recommendations, reference ranges and quantification methods in pictures and tables.